PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN VIDEO TUTORIAL TERHADAP HASIL BELAJAR SENI RUPA DI KELAS VIII SMPN 12 PADANG - BOBI SAPUTRA, Dra. Zubaidah, M.Pd. (Serupa The Journal of Art Education, 2019)
The problem in this study was the low learning of students in drawing models in class VIII of SMP Negeri 12 Padang. The purpose of this study was to determine the effect of using video tutorial learning media on the results of learning art in Class VIII of SMP 12 Padang. This study uses a technique (purposive sampling). After testing the hypotheses obtained in the pretest class obtained tcount 0.260 and t table 1.648 with an average in the experimental class 62.33 and the control class 62.77. So, it can be concluded that there is no significant difference between student learning outcomes from the experimental group and the control group. In the posttest class, tcount was 3,317 and t table 1,648 with the average in the experimental class 80.7 and the control class 76.87. So, it can be concluded that there are significant differences between student learning outcomes from the experimental group and the control group.. It was explained that the use of tutorial video learning media had an effect on the results of learning art in Class VIII of SMP 12 Padang. In order for learning to use the video tutorial to run well, the teacher should first master how to implement the video tutorial.Keywords: Video Tutorial Learning Media and The Results Of Learning